The Role Of Leadership in Human Resources Management in the Digital Government Era - Artanty Utami; Denny Rakhmad Widi Ashari; Slamet Muchsin; Afiffudin Afiffudin; Muhammad Syahrul Hidayat (Indonesian Interdisciplinary Journal of Sharia Economics)
In today's digital era, skilled leadership plays a crucial role in the utilization of information technology. This is in line with the role of human resource management in organizing government operations and public services to run efficiently, especially in the era of digital government. This qualitative study with content analysis reveals the role of leadership in human resource management applied in digital government. The findings of this research are as follows: first, leadership acts as a counselor for government digitalization; second, it serves as an instructor in implementing digital-based public services; third, leaders lead meetings and make decisions using digital technology; and fourth, leadership plays a role in delegating authority using technology and information.